Towards Implementing a Studio Culture Policy in the Department of Architecture of EMU – Students’ Perspective in Understanding Studio Culture - Abualflayeh, Abdallah D. M. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
In the design studio, a predominant learning format to teach design in architectural education, students develop certain ways of doing things when occupying its space with learning activities and interactions that are often referred to as studio culture. In the architectural design studios in the Department of Architecture of EMU, studio culture is the experienced habits and traditions with, assumingly, minimum explicit indication of what constitutes its prime notions. Considering students’ perspectives, the purpose of this study is an attempt to establish an understanding of studio culture within the architectural design studios of EMU and explore the possibility of using this understanding for future implementation of what is known as a studio culture policy within the department’s current and future agenda for accreditation and international certification by organizations such as NAAB, MiAK…etc. To achieve this purpose, the study relied on four synthesized parameters as a base to build up an understanding of studio culture, these are pedagogical perspectives and learning culture, informal interactions of the studio, the physical space of the studio, and the values embedded within the studio. Taking these in mind, a Self-Administrated Questionnaire was used to collect and analyze data through exploratory and sequential mixed methods. From the data, studio culture in the architectural design studios of EMU was understood through twelve developed narratives that discussed these parameters and their interrelations and were situated, through documented considerations, within the process towards. implementing a studio policy in the Department of Architecture of EMU. The significance of this study comes from its bottom-up approach in understanding studio culture and its implementation of a studio policy. Heading up the process of the implementation with students’ perspectives on studio culture might be a fortified base in the process of implementing a reliable studio culture policy for the department. Keywords: Studio Culture Policy; Studio Culture; Architectural Design Studio; Educational Cultures

ÖZ:Mimarlık eğitiminde tasarım eğitimi için baskın bir öğrenim formu olan tasarım stüdyosunda, öğrenciler genellikle stüdyo kültürü olarak adlandırılan öğrenme etkinlikleri ve etkileşimleri ile stüdyo mekanını işgal ederken bir şeyler yapmanın belirli yollarını geliştirirler. DAÜ Mimarlık Bölümü'ndeki mimari tasarım stüdyolarında, stüdyo kültürü, temel kavramlarını neyin oluşturduğuna dair net göstergeler olmadan, deneyimlenen alışkanlıklar ve geleneklerin bütünüdür. Öğrencilerin bakış açısını dikkate alarak, bu çalışmanın amacı, DAÜ mimari tasarım stüdyolarında stüdyo kültürü anlayışı oluşturmaya çalışmak ve bu anlayışın bölüm bünyesinde stüdyo kültürü politikasının yazılı hale gelmesi ile mevcut ve gelecekteki NAAB, MiAK…vb. gibi kuruluşlar tarafından akreditasyon ve uluslararası sertifikasyon için yol haritası oluşturmaktır. Bu amaca ulaşmak için, çalışma bir stüdyo kültürü anlayışını oluşturan dört temel parametreyi içermektedir. Bunlar; pedagojik bakış açıları ve öğrenme kültürü, stüdyonun informel etkileşimleri, stüdyonun fiziksel alanı ve içerdiği değerler bütünüdür. Bunları göz önünde bulundurarak, araştırma ve ardışık karma yöntemlerle veri toplamak ve analiz etmek için bir anket kullanılmıştır. Verilerden, DAÜ'nün mimari tasarım stüdyolarındaki stüdyo kültürü, bu parametreleri ve aralarındaki ilişkileri tartışan on iki gelişmiş anlatı aracılığıyla belirlenmiş ve DAÜ Mimarlık Bölümü'nde bir stüdyo politikasının uygulanmasına yönelik süreç içinde bir yol haritası önerilmiştir. Bu çalışmanın önemi, stüdyo kültürünü anlamadaki aşağıdan yukarıya yaklaşımından ve buna bağlı bir stüdyo politikasının oluşturulmasının önerilmesidir. Uygulama sürecini öğrencilerin stüdyo kültürüne bakış açısıyla yönlendirmek, bölüm için güvenilir bir stüdyo kültürü politikası uygulama sürecinde sağlam bir temel olabilir. Anahtar Kelimeler: Stüdyo Kültürü Politikası; Stüdyo Kültürü; Mimari Tasarım Stüdyosu; Eğitim Kültürleri
Master of Science in Architecture. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2021. Supervisor: Prof. Dr. Özgür Dinçyürek
Keywords: Architecture-Studio Culture-Studio Policy-Study and Teaching; Architectural design-Study and teaching-Architectural Education-Eastern Mediterranean University-Cyprus, North; Architectural studios; Studio Culture Policy; Studio Culture; Architectural Design Studio; Educational Cultures